UV SPECTROPHOTOMETRIC DETERMINATION OF pK’s OF 1,2,4-TRIAZOLINE-3-THIONES IN SODIUM HYDROXIDE SOLUTIONS - Dimova, Vesna; Jordanov, Igor; Dimitrov, Lazo (Journal of the Chilean Chemical Society, 2016)
Using UV spectroscopy the dissociation constants of previously synthesized 4,5-disupstituted-1,2,4-triazoline-3-thiones are determinate. The UV spectra were recorded in aqueous sodium hydroxide solutions at different pH values in the range from 190 to 360 nm, immediately after preparation of the suspension. The pKTH values were obtained experimentally, graphically and by the Characteristic Vector Analysis method. Results show that the investigated compounds have two dissociation processes. The first process belongs to the dissociation of SH proton, while the second dissociation process is dissociation of OH proton.